The heart of music - Sullon Ramos, Alison Yane (2019)
Music transmits emotions and communicates messages in different ways, therefore, there is a relationship between the two. Music has a significant influence on the life of each person, internalizing their memories, experiences and others. It is known that communication is the basis of human development and relationships between all people. In short, music brings people together, cheers them up or comforts them, but always conveys a message.